Effect of Sodium Carboxymethyl Cellulose from Delonix regia Sawdust on rheological and filtration properties of water based drilling fluid (2021)
Over the past years, there has been an increase in the importation of Sodium Carboxymethyl cellulose (CMC), an important drilling mud polymer additive, in the Nigerian oil and gas industry. However, the ripple effects of the importation of this polymer and other oilfield chemicals on the Nigeria oil and gas industry includes rising cost of oil and gas field development, limited oil and gas industry growth, and capital flight. In order to mitigate this trend, studies on the use of local substitutes such as starch and its derivatives have gathered momentum with risk such as competition with food supply and increase in food cost. The use of sawdust wastes which offers a non-competing and a cheap source of feedstock in the production of CMC have rarely been investigated. The study therefore investigated production of CMC from sawdust waste of a highly underutilized wood (Delonix regia), after which drilling mud tests were conducted to determine the rheological and filtration properties of mud treated with the CMC products. The CMC production adopted the Williamson ether synthesis process in a slurry medium involving two main reactions of mercerization and etherification. All reaction parameters were held constant except the etherifying agent concentration. The CMC products were characterized using FTIR Spectroscopy. The synthesized carboxymethyl cellulose products yielded good filtration and rheological properties suitable for drilling fluid applications. The use of low concentrations of about 0.5g to 1.0g of the synthesized products per laboratory barrel of mud could reduce filtration volume by 11.4% to 32.9% at low temperature and pressure conditions. The synthesized CMC products obtained from this work can be used as local substitute of low viscosity foreign CMC products.